Virotherapy of digestive tumors with rodent parvovirus: overview and perspectives. (3rd May 2016) - Akladios, Cherif; Aprahamian, Marc
ABSTRACT: Introduction : Toolan's H-1 parvovirus (H-1PV) exerts a cytotoxic/oncolytic effect, predominantly mediated by its non-structural protein (NS1). This rat parvovirus is harmless, unlike other parvoviruses, and its antitumor potential may be useful to clinicians as its oncolytic action appears to be true in numerous non-digestive and digestive cancers. Areas covered : After a brief review of parvovirus genus and biology, we summarize the proposed mechanisms to explain the cytotoxicity of H-1PV to tumors which results in dysregulation of cell transcription, cell-cycle arrest, termination of cell replication, activation of cellular stress response and induction of cell death. Viral oncolysis induces a strong tumor-specific immune response leading to the recognition and elimination of minimal residual disease. As the action of H-1PV is not limited to the digestive tract, we initially analyse studies performed in non-digestive cancers such as glioma (as the virus is able to cross the blood brain barrier), and then focused more particularly on the results in digestive cancers. Expert opinion : Based on the results of studies showing little H-1PV toxicity to living bodies, we advocate for the use of the parvovirus in cancers such as melanoma, glioma and pancreatic ductal adenocarcinoma in addition to conventional chemotherapy.